2003
DOI: 10.1029/2003gl018848
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pure silica coatings on thermal emission spectra of basaltic rocks: Considerations for Martian surface mineralogy

Abstract: [1] On Mars, silica derived from chemical weathering could precipitate to coat rocks and particles. We suggest that rock coatings of secondary amorphous silica may account for a widespread Martian surface spectral unit previously modeled as andesite or weathered basalt. In a laboratory study, we investigated the effects of synthetic silica coatings on thermal infrared (TIR) spectroscopic measurements. Secondary amorphous silica is spectrally similar to silicate glass and clay spectra used in previous spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
114
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 26 publications
9
114
0
Order By: Relevance
“…The units probably consist of a variety of materials including loess-like deposits [Skinner et al, 2012], sediments, lavas and/or volcaniclastic materials, yet the signals of hydrated or mafic mineralogy are not observed using CRISM data. Puzzling as it is, we suggest that the "bland" VSWIR spectral features of the upper layer may be due to either weathering products of basaltic glass with silica-enriched rinds [Kraft et al, 2003;Horgan and Bell, 2012] or alteration coatings of optically active Fe minerals in basalt, analogous to those observed at Gusev crater [McSween et al, 2006;Mustard et al, 2005;Salvatore et al, 2010]. Alternatively, these features may be due to poorly crystalline phases dominating the spectral properties, similar to the abundant amorphous material in unconsolidated sediments as well as sedimentary rocks within Gale crater as explored by the Curiosity rover [e.g., Blake et al, 2013;Bish et al, 2014].…”
Section: Mineralogy Of the Upper Layer Of The Northern Lowlandsmentioning
confidence: 81%
See 3 more Smart Citations
“…The units probably consist of a variety of materials including loess-like deposits [Skinner et al, 2012], sediments, lavas and/or volcaniclastic materials, yet the signals of hydrated or mafic mineralogy are not observed using CRISM data. Puzzling as it is, we suggest that the "bland" VSWIR spectral features of the upper layer may be due to either weathering products of basaltic glass with silica-enriched rinds [Kraft et al, 2003;Horgan and Bell, 2012] or alteration coatings of optically active Fe minerals in basalt, analogous to those observed at Gusev crater [McSween et al, 2006;Mustard et al, 2005;Salvatore et al, 2010]. Alternatively, these features may be due to poorly crystalline phases dominating the spectral properties, similar to the abundant amorphous material in unconsolidated sediments as well as sedimentary rocks within Gale crater as explored by the Curiosity rover [e.g., Blake et al, 2013;Bish et al, 2014].…”
Section: Mineralogy Of the Upper Layer Of The Northern Lowlandsmentioning
confidence: 81%
“…Thermal infrared data acquired from Thermal Emission Spectrometer (TES) indicate a relatively silica-enriched surface (surface type II) compared to the typical basalt (Surface type I) of the southern highlands [Christensen et al, 2001]. Therefore, the surface of the lowlands was initially interpreted to be andesitic in composition [Bandfield et al, 2000] but later reinterpreted to represent altered terrains [e.g., Wyatt and McSween, 2002;Kraft et al, 2003;Michalski et al, 2005]. Gamma Ray Spectrometer data do not show enhancement of Si in the bulk rock [Karunatillake et al, 2006;Boynton et al, 2007], thus favoring the interpretation that spectral differences may be explained by the presence of a thin silica-enriched coating or rind [e.g., Kraft et al, 2003].…”
Section: History and Composition Of The Northern Lowlandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some TES analyses revealed that high-silica phase(s) could be one of the significant mineral groups for many low albedo regions. Primary high-silica volcanic glasses are potentially indistinguishable from some secondary amorphous or poorly crystalline high-silica materials in the thermal infrared spectral region (Bandfield, 2002;Wyatt and McSween, 2002;Kraft et al, 2003;Michalski et al, 2003;Morris et al, 2003;Ruff, 2004;Koeppen and Hamilton, 2005), which complicates the interpretation of high-silica phase(s) detected by the TES instrument. OMEGA detects hydrated minerals including phyllosilicates in some specific geological units that are disconnected from the low albedo mafic-rich regions .…”
Section: Accepted M Manuscriptmentioning
confidence: 99%